Mitochondrial Control and Guidance of Cellular Activities of T Cells - Chao, Tung; Wang, Haiping; Ho, Ping-Chih (Frontiers in Immunology, 2017)
Immune cells protect us against infection and cancer cells, as well as functioning during healing processes to support tissue repairing and regeneration. These behaviors require that upon stimulation from immune activation the appropriate subsets of immune cells are generated. In addition to activation-induced signaling cascades, metabolic reprogramming (profound changes in metabolic pathways) also provides a novel form of regulation to control the formation of desirable immune responses. Immune cells encounter various nutrient compositions by circulating in bloodstream and infiltrating into peripheral tissues; therefore, proper engagement of metabolic pathways is critical to fulfill the metabolic demands of immune cells. Metabolic pathways are tightly regulated mainly via mitochondrial dynamics and the activities of the tricarboxylic acid cycle and the electron transport chain. In this review, we will discuss how metabolic reprogramming influences activation, effector functions, and lineage polarization in T cells, with a particular focus on mitochondria-regulated metabolic checkpoints. Additionally, we will further explore how in various diseases deregulation and manipulation of mitochondrial regulation can occur and be exploited. Furthermore, we will discuss how this knowledge can facilitate the design of immunotherapies.